FC054: Voclosporin for Lupus Nephritis: Results of the Two-Year Aurora 2 Continuation Study. (3rd May 2022) - Teng, Y.K.O.; Saxena, Amit; Palmen, Mary; Birardi, Vanessa; Lisk, Laura
Abstract: BACKGROUND AND AIMS: Voclosporin, a novel calcineurin inhibitor, was approved in the USA in January 2021 for the treatment of adult patients with active lupus nephritis in combination with background immunosuppressive therapy. Voclosporin has a favorable metabolic profile and a consistent dose-concentration relationship, eliminating the need for therapeutic drug monitoring. Previously reported results from the Phase 2 AURA-LV and Phase 3 AURORA 1 studies showed that the addition of voclosporin to mycophenolate mofetil (MMF) and low-dose steroids in patients with lupus nephritis significantly increased rates of complete renal response at 48 weeks (AURA-LV) and 52 weeks (AURORA 1). Here we report the results of the completed continuation study, AURORA 2, which assessed the long-term safety and tolerability of voclosporin compared with placebo in patients with lupus nephritis receiving treatment for an additional 24 months following completion of the AURORA 1 study. METHOD: Key inclusion criteria for the parent AURORA 1 study included a diagnosis of biopsy-proven active lupus nephritis (Class III, IV, or V ± III/IV), proteinuria ≥ 1.5 mg/mg (≥2 mg/mg for Class V) and estimated glomerular filtration rate (eGFR) ≥45 mL/min/1.73 m 2 . Patients who completed AURORA 1 were eligible to enroll in AURORA 2 and continued with the same blinded treatment of voclosporin (23.7 mg BID) or placebo in combination with MMF (target dose 2 g/day) and low-dose oral steroids. Safety and tolerability were evaluated by monitoring adverse events and laboratory assessments including eGFR; changes in urine protein creatinine ratio (UPCR) were also assessed. RESULTS: In total, 116 patients in the voclosporin arm and 100 patients in the control arm enrolled in AURORA 2, with 92 (79.3%) and 73 (73.0%) patients in each respective arm completing treatment to the end of AURORA 2. There were no new or unexpected safety signals detected in patients who continued on treatment with voclosporin compared to control-treated patients. Rates of serious adverse events in the voclosporin (19.0%) and control arms (24.0%) were similar, with eight serious adverse events of infection in each arm. Estimated glomerular filtration rate remained stable through the end of AURORA 2 (Figure 1 ). The slopes of the least-squares (LS) mean change in corrected eGFR from AURORA 2 baseline to end of study were –0.2 [95% confidence interval (CI) –3.0 to 2.7' in the voclosporin arm and –5.4 (95% CI –8.4 to –2.3) in the control arm. There were no deaths in the voclosporin arm during AURORA 2; four deaths were reported in the control arm due to pulmonary embolism ( n  = 1) and coronavirus infection ( n  = 3). The LS mean reductions in UPCR observed in AURORA 1 were maintained in AURORA 2 with no increase in UPCR noted at the follow-up visit 4 weeks after study drug discontinuation (Figure 2 ). CONCLUSION: Voclosporin was well-tolerated over three years of treatment with a similar safety profile to control and no unexpected safety signals detected. Further, the significant and meaningful reductions in proteinuria initially achieved in AURORA 1 were maintained throughout AURORA 2. These data provide evidence of a long-term treatment benefit of voclosporin in patients with lupus nephritis.